Evaluasi Kinerja Proyek Pemeliharaan Jalan Menggunakan Metode Earned Value Management (EVM) - Novi Nur Ma’rifatul Qomariah; Eriska Fitri Kurniawati (Universitas Ma'arif Lampung, 2026)
This research aims to analyze the cost and time performance of the Bojonegoro–Ponco road maintenance project using the Earned Value Management (EVM) method. This method is used to evaluate project achievement by comparing the Planned Value (PV), Earned Value (EV/BCWP), and Actual Cost (AC) to determine cost efficiency and schedule accuracy. . The data used is secondary data in the form of project progress reports for eight weeks of implementation. The analysis results show that the Cost Performance Index (CPI) value during the observation period is below 1, indicating that the project experienced cost inefficiency and is likely to have cost overrun. This is reinforced by the Estimate at Completion (EAC), which is around Rp180–190 million, higher than the initial contract value of Rp156,511,000. In terms of schedule, the Schedule Performance Index (SPI) is also below 1, indicating delays in work implementation. The Estimate at Schedule (EAS) shows a significant potential delay compared to the initial plan. The contribution of this study lies in the comprehensive application of the Earned Value Management (EVM) method to evaluate the performance of road maintenance projects, thereby providing a quantitative overview of cost efficiency and schedule adherence, as well as serving as a basis for decision-making in construction project control. Future research is recommended to further examine the factors causing cost inefficiencies and delays in greater depth, and to combine the EVM method with other project management methods in order to obtain more optimal and accurate analysis results.